The Impact of Competition Policy Enforcement on the Functioning of EU Energy Markets - Tomaso Duso; Jo Seldeslachts; Florian Szucs (The Energy Journal, 2019)
We investigate the impact of competition policy enforcement on the functioning of European energy markets while accounting for sectoral regulation. For this purpose, we compile a novel dataset on the European Commission's (EC) and EU member states' competition policy decisions in energy markets and combine it with firm- and sector-level data. We find that EC merger policy has a positive and robust impact on (i) the level of competition, (ii) investment and (iii) productivity. This impact, however, only shows up in low-regulated sectors. Other competition policy tools - EC state aid control and anti-trust, as well as all member state policy variables - do not have a uniform effect on energy markets. Our findings are consistent with the idea that the EC's merger policy actions have been used to overcome obstacles to a well-functioning EU energy sector and may have contributed to the overall development of gas and electricity markets in Europe.
Keywords: 330; Ex-post; evaluation; competition; policy; energy market